2018
DOI: 10.1002/jwmg.21486
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral response of canada geese to egg‐oiling and nest removal

Abstract: Controlling overabundant goose populations remains a wildlife management challenge. Although reducing adult survival is considered more effective than reducing fecundity, egg‐oiling, and egg removal are often preferential techniques for controlling temperate nesting Canada geese (Branta canadensis) in urban and peri‐urban settings. Little is known about the effect of these methods on the subsequent behavior of geese and their potential effects on population dynamics. We aimed to determine how long Canada geese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
(18 reference statements)
1
15
0
Order By: Relevance
“…, Beaumont et al. ). Concordantly, our observations revealed that no nesting pairs immediately abandoned their nests following our treatment with the RFAS, even when 100% of the oiled nests went on to fail.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, Beaumont et al. ). Concordantly, our observations revealed that no nesting pairs immediately abandoned their nests following our treatment with the RFAS, even when 100% of the oiled nests went on to fail.…”
Section: Discussionmentioning
confidence: 99%
“…However, nest site fidelity in Canada goose ( Branta canadensis ) was found to be unaffected by oiling the previous year (Beaumont et al. ). This result suggests that oiling may be used year‐on‐year while birds defend home territories before they decide (if ever) to nest elsewhere (Beaumont et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We marked each surplus egg on either end with a non‐toxic felt‐tip marker and then, following an egg‐addling technique commonly used to control populations of waterfowl (e.g., Beaumont et al. ), coated eggs with olive oil to prevent gas exchange. We chose to addle surplus eggs rather than use live eggs because too few nests were available overall to always have access to surplus eggs that were at the same stage of development as eggs in experimental nests.…”
Section: Methodsmentioning
confidence: 99%